Upaya Penanganan Pembiayaan Bermasalah pada KSPPS BMT An Nur Purworejo Periode 2011-2015 - Mir'atul Fadlilliyah (FAI, 2017)
Upaya Penanganan Pembiayaan Bermasalah pada KSPPS BMT An Nur Purworejo Periode 2011-2015